Snakebite drug discovery: high-throughput screening to identify novel snake venom metalloproteinase toxin inhibitors - Clare, Rachel H.; Dawson, Charlotte A.; Westhorpe, Adam; Albulescu, Laura-Oana; Woodley, Christopher M.; Mosallam, Nada; Chong, Daniel J. W.; Kool, Jeroen; Berry, Neil G.; O’Neill, Paul M.; Casewell, Nicholas R. (Frontiers in Pharmacology, 2024)
Snakebite envenoming results in ~138,000 deaths per year, with close to four times as many victims left with life-long sequelae. Current antivenom therapies have several limitations including high cost, variable cross-snake species efficacy and a requirement for intravenous administration in a clinical setting. Next generation snakebite therapies are being widely investigated with the aim to improve cost, efficacy, and safety. In recent years several small molecule drugs have shown considerable promise for snakebite indication, with oral bioavailability particularly promising for community delivery rapidly after a snakebite. However, only two such drugs have entered clinical development for snakebite. To offset the risk of attrition during clinical trials and to better explore the chemical space for small molecule venom toxin inhibitors, here we describe the first high throughput drug screen against snake venom metalloproteinases (SVMPs)a pathogenic toxin family responsible for causing haemorrhage and coagulopathy. Following validation of a 384-well fluorescent enzymatic assay, we screened a repurposed drug library of 3,547 compounds against five geographically distinct and toxin variable snake venoms. Our drug screen resulted in the identification of 14 compounds with pan-species inhibitory activity. Following secondary potency testing, four SVMP inhibitors were identified with nanomolar EC50s comparable to the previously identified matrix metalloproteinase inhibitor marimastat and superior to the metal chelator dimercaprol, doubling the current global portfolio of SVMP inhibitors. Following analysis of their chemical structure and ADME properties, two hit-to-lead compounds were identified. These clear starting points for the initiation of medicinal chemistry campaigns provide the basis for the first ever designer snakebite specific small molecules.